Food Hypersensitivity in Children Aged 0–3 Years of the Lviv Region in Ukraine: A Cross-Sectional Study - Matsyura, Oksana; Besh, Lesya; Borysiuk, Olena; Gutor, Taras; Malska, Andriana; Kovalska, Oksana; Besh, Olesia; Sorokopud, Olena; Vari, Sandor G. (Frontiers in Pediatrics, 2022)
Aim. To determine the prevalence and to estimate factors associated with food hypersensitivity in young children of the Lviv region in Ukraine. Methods. A prospective cross-sectional survey study was conducted between 2016-2017 in the Lviv region of Ukraine. A specially designed questionnaire about food hypersensitivity of young children developed and validated by M. J. Flokstra-de Blok was used after translation into the Ukrainian language. The questionnaire included 34 questions, grouped into general and detailed information. Parents of children aged 0 to 3 years were asked to complete the questionnaire at pre-schools and medical institutions. Results. Among 4500 distributed questionnaires, 3214 (71%) were completed and processed. Parents reported that 25% of their young children had food hypersensitivity. According to the survey the most common agents involved in food hypersensitivity in young children were cow’s milk (34%), egg (28%), and wheat (24%). Hypersensitivity to milk occurred in 50% of children in the age group of 1-2 years. Regional differences associated with food hypersensitivity were also found. Namely, in the Carpathians, there was more hypersensitivity to fish (27%) and honey (22%) than in other regions, while hypersensitivity to soy was detected mostly in Lviv City residents (8.5%). Unknown causes of food hypersensitivity were highly reported (34%) in the Carpathians. Conclusion. Prevalence and some distinctiveness of food hypersensitivity revealed in four geographic and climate zones as well as in Lviv City have a considerable practical use for formulation of recommendations for children with food hypersensitivity.